Leadership and Subordinate Engagement in Transforming Islamic Higher Education Institutions to Advance the SDGs: Evidence from Central Java - Edy Muslimin; Giyoto; Yusup Rohmadi (Profetika: Jurnal Studi Islam, 2025)
Objective: This study explores the leadership transformation of Islamic higher education institutions (Perguruan Tinggi Keagamaan Islam Swasta/PTKIS), focusing on the Mamba'ul 'Ulum Islamic Institute Indonesia (IIMU) from 2020 to 2025. Theoretical framework: Anchored in the theory of democratic leadership in Islamic education, the study emphasizes participation, authority distribution, and inclusivity as key pillars for organizational transformation. Literature review: A literature review highlights the relevance of transformational, participatory, structural, and cultural dimensions in shaping effective leadership in Islamic educational settings. Methods: The research employs a qualitative case study method, utilizing in-depth interviews, participatory observations, and document analysis. The participants include institutional leaders, lecturers, and staff across different departments at IIMU. Results: Findings reveal that although IIMU adopts a democratic leadership style in principle, the actual involvement of subordinates in strategic decision-making and program implementation remains minimal. Structural hierarchies, centralized decision-making practices, and entrenched work cultures present significant barriers. Nonetheless, where subordinate engagement is enhanced, there is a notable improvement in managerial efficiency and the overall quality of educational programs. In alignment with Sustainable Development Goal (SDG) 4, which promotes inclusive and equitable quality education and lifelong learning opportunities for all, this study underlines the importance of collaborative governance in Islamic education. Implications: It suggests that strengthening participatory leadership could support institutional innovation, accountability, and inclusive development. Furthermore, promoting internal dialogue and professional empowerment aligns with SDG 16, which calls for effective, accountable, and inclusive institutions. Novelty: The study’s novelty lies in its contribution to the discourse on democratic values in Islamic education leadership, particularly in PTKIS transformation. It highlights how empowering subordinates can enhance educational service delivery and institutional sustainability. These insights are vital for stakeholders aiming to align Islamic higher education with national education reforms and global development agendas such as the SDGs.